Występowanie jeżyn ( Rubus L.) w młodych uprawach leśnych na Płaskowyżu Kolbuszowskim - Wolanin, Mateusz; Oklejewicz, Krzysztof; Wolanin, Magdalena (Leśne Prace Badawcze, 2017)
In the Kolbuszowa Plateau forest areas, aggregations of brambles were observed most often in young forest plantations and forest clear cuts. In the 20 plantations that we examined, 11 bramble species were found. The most common bramble species in young forest plantations were Rubus plicatus, R. nessensis, R. hirtus, R. idaeus and more rarely R. gracilis, R. ambrosius and R. apricus . The largest bramble aggregations occurred in plantations located in mixed pine-oak forests, subcontinental lime-oakhornbeam forests and drained black alder forests. In young forest plantations the Rubus species were accompanied by species characteristic for the Vaccinio-Piceetea , Querco-Fagetea , Epilobietea angustifolii , Molinio-Arrhenatheretea and Nardo-Callunetea associations. There are three groups of bramble species which occur in young forest plantations: I – species with thin, prostrate and rooting stems ( R. hirtus , R. apricus , R. pedemontanus ), the negative impact of which on tree seedlings could have been very significant if the bramble specimens or diaspores had been present at the moment of tree planting; II – species with strong, poorly branched and arched stems ( R. plicatus , R. gracilis , R. ambrosius , R. glivicensis ), which negative influence on tree seedlings depends on the capability of the species to produce a big, dense bush in a short period of time thereby increasing shade; III – species with erect and relatively sparsely growing stems ( R. idaeus ), which are not a threat for the young forest plantations. Species with intermediate features (e.g. R. nessensis ) may have a negative impact on young plantations generating a large, dense aggregation, however in most cases their populations only grow sparsely and do not hinder the growth of tree seedlings.